Literature Review: The Role of Advertising in Building Brand Awareness - Rafika Zahwa Alifia; Cecep Safa'atul Barkah; Iwan Sukoco; Lina Auliana (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Brand awareness is an important element in brand equity that indicates consumer knowledge of the existence of a brand. In building brand awareness, many companies use advertising to provide information about the products or services they offer. Finding out how the role of using advertising through various media in developing consumer brand awareness is the purpose of this study. Literature Review is the method used in which the author writes articles based on previous studies in the sphere of advertising and brand awareness. From these studies, it can be concluded that advertising has a significant role in building brand awareness and the effectiveness of advertising in building brand awareness is achieved if it meets several indicators, namely attracting, attracting attention, encouraging a sense of desire, and making consumers take action.